MANAJEMEN WAKAF UANG PADA YAYASAN YATIM MANDIRI - Liana Dewi (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2019)
One of the Islam’s doctrine is requires every Muslim always to do good deeds in all conditions and situations. One realization of that is givesome of his property (wakaf). In Law Number 41 of 2004, the issue of cash wakafwas set specifically in the tenth part, thewakaf’s moving object in the form of cash in article 28th stated, wakif can give moving objects of money through the institution of sharia money. Based on that law, the chances of development of the productive wakaf withcash wakaf open widely, one of the priority channeling of cash wakaf is the education’s cost of poor children. In fact in socialization Zisco (zakat donations sadakah consultant) / interpreter adoptee can be nadzir that accept cash wakaf for construct Ulul Asbab mosque and Insan Cendekia boarding school if there is someone will donate cash wakaf. The accumulationof cash wakafin Yatim Mandiri foundation is suitable with the purpose of wakaf’s fundraising those areaccumulate funds, adds the candidate of wakif, improve or build image of Institute, Collecting Investigators / relation and supporters, improve wakif’s satisfaction. Management and Distribution of cash wakafin Yatim Mandiri foundation has notwakaf’s productivity, although there has been financing that the results can be distributed to mauquf alaih. However the currently wakaf channeled directly based on accordance such as cash wakaf for construction and land acquisition ICMBS, building Ulul Albabmosque, to purchase the Koran and wakaf Rumah Kemandirian.